In-Situ Test Method for Hydrodynamic Characteristics of Water Flowing Around Piles - Liu, Mingwei; Zeng, Liqin; Wu, Linjian; Chen, Gang; Shen, Lilong; Abi, Erdi (Frontiers in Environmental Science, 2022)
The dynamic characteristics of the flow around the pile directly determine the distribution law of the force of the flow on the pile, which is the basis of the calculation of the flow load of the hydraulic structure. At present, the model test and numerical simulation methods are mainly used to study the flow characteristics around the pile. There are problems of model scale effect and test accuracy in the laboratory model test, and inherent problems in the numerical simulation method, such as the determination of medium parameters, mesh division, and boundary conditions. Therefore, the research results cannot reflect the actual situation of the interaction between water flow and pile. This paper developed a field test system for measuring the hydrodynamic pressures on surface of piles which are the vital foundations of wharves under superhigh Reynolds number. And the analysis methods of in-situ data, which can realize the multifunction including calibration and transformation for test data, frequency and time-domain statistical analysis process, were put forward according to the theory of stationary random process and mathematical statistics method. A representative frame wharf located in the upper reaches of the Yangtze River was performed as a case study, and the developed system was utilized to operate the in-situ test on this practice. Application showed that the field test system and the analysis methods can be applied to obtain the more accurate distribution of the pile surface hydrodynamic pressure. And the drag coefficient in wharf field ranged from 0.30 to 0.40. These findings in this paper may provide significant technical support for the in-situ test in similar structures and some reference for drag force calculation of flow around pile in the engineering design.